Cheong-sang-bang-pung-san alleviated hepatic lipid accumulation by regulating lipid metabolism in vitro and in vivo - Kang, Yun-Mi; Kim, Kwang-Youn; Kim, Tae In; Kim, Yeon-Ji; Kim, Han-Hae; Kim, Kyungho (Frontiers in Pharmacology, 2023)
Introduction: The occurrence of fatty liver disease, resulting from the accumulation of excessive fat within the liver, has been showing a significant and rapid increase. This study aimed to evaluate the therapeutic effects of Cheong-sang-bang-pung-san extract (CB) on fatty liver disease, and to elucidate the underlying mechanisms. Methods: We used a high-fat diet (HFD)-fed fatty liver mice and free fatty acid (FFA) induced HepG2 cell lipid accumulation model. The levels of serum, hepatic, and intracellular lipid content were assessed. Histopathological staining was used to evaluate the extent of hepatic lipid accumulation. Real-time polymerase chain reaction and Western blotting were conducted to examine the expression of factors associated with lipid metabolism. Results: We demonstrated that treatment with CB dramatically reduced body weight, liver weight, and fat mass, and improved the serum and hepatic lipid profiles in HFD-induced fatty liver mice. Additionally, CB alleviated lipid accumulation in HFD-fed mice by controlling lipid metabolism, including fatty acid uptake, triglyceride and cholesterol synthesis, and fatty acid oxidation, at the mRNA as well as protein levels. In free fatty acid-treated HepG2 cells, CB significantly reduced intracellular lipid accumulation by regulating lipid metabolism via the activation of AMP-activated protein kinase. Conclusion: These findings provide insights into the mechanisms underlying CB's effects on liver steatosis and position of CB as a potential therapeutic candidate for managing lipid metabolic disorders.